A Terrestrial Gamma‐Ray Flash From the 2022 Hunga Tonga–Hunga Ha'apai Volcanic Eruption. Issue 14 (21st July 2022) - Briggs, M. S.; Lesage, S.; Schultz, C.; Mailyan, B.; Holzworth, R. H.
Abstract: The Hunga Tonga–Hunga Ha'apai submarine volcano recently resumed activity. Violent eruptions on 14th and 15th January 2022 launched a tall ash plume that produced extremely high lightning rates. Here we report a terrestrial gamma‐ray flash (TGF) that was produced by the volcanic lightning and observed from space by the Fermi Gamma‐ray Burst Monitor (GBM). Observations by radio lightning networks and especially by the Geostationary Lightning Mapper show that the only lightning close enough to produce a TGF detectable by Fermi GBM was from the volcano's plume. With the observing duration of Fermi, observing a single TGF is consistent with the hypothesis that the volcanic lightning of this eruption produced TGFs at the average rate of thunderstorm lightning. The observation of a strong TGF from space also indicates that the electric field was oriented so as to accelerate electrons upward. Plain Language Summary: Terrestrial Gamma‐ray Flashes (TGFs) are short, intense flashes of gamma‐ray that are associated with lightning. Until now these flashes have only been associated with thunderstorms. High electric fields in thunderstorms accelerate electrons, which then produce gamma‐rays that are observed by space‐based detectors. On 14th and 15th January 2022 violent eruptions of the Hunga Tonga–Hunga Ha'apai volcano produced extremely high lightning rates. NASA's Fermi Gamma‐ray Burst monitor detected a TGF from this lightning, showing that volcanic lightning can also produce TGFs. Any storm with electric fields strong enough to accelerate electrons to high energies is able to produce gamma‐ray flashes. Key Points: A terrestrial gamma‐ray flash (TGF) was detected from volcanic lightning from Hunga Tonga–Hunga Ha'apai, extending the types of storms that can produce TGFs The observation of a single TGF is consistent with the volcanic lightning producing TGFs at the same rate as thunderstorm lightning The observation of the TGF from space indicates that electrons were accelerated upward by the electric field within the volcanic plume